Acute effects of drop jump potentiation protocol on sprint and countermovement vertical jump performance - Bomfim Lima, J. C.; Popp Marin, D.; Barquilha, G.; Ortega da Silva, L.; Puggina, E. F.; Pithon-Curi, T. C.; Hirabara, S. M. (Human Movement, 2011)
Purpose. Muscle post-activation potentiation (PAP) is a mechanism by which power twitch is increased after previous conditioning contractions. In this study, we determined the time-dependent effect of a loaded drop-jump protocol on sprint time and countermovement jump height in well-trained athletes. Methods. Ten athletes randomly performed the control and experimental protocols on two different days. As a pre-test, the athletes performed the vertical jump and 50 m sprint test for preload measurements. Then, the experimental or control protocol was randomly applied, where the control protocol was composed of the athletes remaining at rest for 10 min. In the experimental protocol, the athletes performed two sets of 5 drop jumps (0.75 m), with a 15 s interval between the jumps and a 3 min rest after each set. Then the vertical jump and 50 m sprint tests were performed again 5, 10, and 15 min after the protocol. Results. The experimental condition (drop jump potentiation protocol) increased performance in the vertical jump by 6% after 15 min (p < 0.01) and in the sprint by 2.4% and 2.7% after 10 and 15 min, respectively (p < 0.05). Conclusions. These findings suggest that the drop jump potentiation protocol increases countermovement vertical jump and sprint performance in high-performance athletes at different times, suggesting that PAP induction depends not only on the design of the protocol, but also on the effect of time and the type of exercise involved.